Managing Social Research - Tarling, Roger (Social Research Today, 2006)
An essential tool for those planning to undertake social research, this exceptional book tackles many of the specific concerns and issues that arise. A well structured text, it offers a comprehensive introduction to a range of important areas in project management, including: commissioning research preparing a tender or grant application risk and stakeholder analysis managing the field work and data analysis financial management ethics, confidentiality and copyright. This book provides a unique source of guidance for anyone seeking to commission, manage or carry out social research. It will especially benefit researchers working in a variety of different contexts, including those in academia, central or local government, 'quangos', public bodies or private consulting companies.